Functional and Structural Diversity of Bacterial Contact-Dependent Growth Inhibition Effectors - Cuthbert, Bonnie J.; Hayes, Christopher S.; Goulding, Celia W. (Frontiers in Molecular Biosciences, 2022)
Bacteria live in complex communities and environments, competing for space and nutrients. Within their niche habitats, bacteria have developed various inter-bacterial mechanisms to compete and communicate. One such mechanism is contact-dependent growth inhibition (CDI). CDI is found in many Gram-negative bacteria, including several pathogens. These CDI+ bacteria encode a CdiB/CdiA two-partner secretion system that delivers inhibitory toxins into neighboring cells upon contact. Toxin translocation results in the growth inhibition of closely related strains and provides a competitive advantage to the CDI+ bacteria. CdiB, an outer-membrane protein, secretes CdiA onto the surface of the CDI+ bacteria. When CdiA interacts with specific target-cell receptors, CdiA delivers its C-terminal toxin region (CdiA-CT) into the target-cell. CdiA-CT toxin proteins display a diverse range of toxic functions, such as DNase, RNase, or pore-forming toxin activity. CDI+ bacteria also encode an immunity protein, CdiI, that specifically binds and neutralizes its cognate CdiA-CT, protecting the CDI+ bacteria from auto-inhibition. In Gram-negative bacteria, toxin/immunity (CdiA-CT/CdiI) pairs have highly variable sequences and functions, with over 130 predicted divergent toxin/immunity complex families. In this review, we will discuss biochemical and structural advances made in the characterization of CDI. This review will focus on the diverse array of CDI toxin/immunity complex structures together with their distinct toxin functions. Additionally, we will discuss the most recent studies on target-cell recognition and toxin entry, along with the discovery of a new member of the CDI loci. Finally, we will offer insights into how these diverse toxin/immunity complexes could be harnessed to fight human diseases.